THE PREOPERATIVE MANAGEMENT OF THE OXYGEN TRANSPORT IN THE PATIENTS WITH ACUTE ADHESIVE SMALL BOWEL OBSTRUCTION - M. I. Neymark; A. S. Zhukov (Вестник анестезиологии и реаниматологии, 2017)
The comparative judgment of the preoperative fluid therapy was performed with 56 acute small bowel obstruction patients. The parameters of the oxygen delivery and the central hemodynamics were tested. It is shown that the fluid therapy conducted for 3 hours with the balanced colloidal and crystalloid solutions for a median of 500 and 2000 ml correspondingly reverses the hemodynamic dislocations, regulates the management of the oxygen delivery and to some extent improves the surgical results.